A cyber-physical scheme for predicting tool wear based on a hybrid dynamic neural network. (3rd October 2017) - Yang, Haw-Ching; Li, Yu-Yung; Hung, Min-Hsiung; Cheng, Fan-Tien
Abstract: It is costly to predict tool wear under various machining conditions. To address this challenge, a tool cyber-physical prediction (TCPP) scheme and a hybrid dynamic neural network (HDNN) model are proposed in this paper. This scheme enables users to build and use the models both in the cloud and at the factory by integrating the theoretical maximum tool life and the practical sensing features of the tool wear. Moreover, using features extracted from the sensors and controller, the HDNN model integrates the logistic regression and dynamic neural network to diagnose the tool break and predict tool wear simultaneously. In addition, the scheme presents a model-refreshing approach to tune the HDNN model to adapt to physical variation of the tool coating, the workpiece material, and the removal process in the similar cutting conditions. The experimental results demonstrate that the TCPP scheme with the HDNN model is promising for tool wear prediction while using only a few samples and the current features to adapt to various cutting conditions.